Production of a Heterologous Recombinant Protein Using Fragments of the Glyceraldehyde-3-Phosphate Dehydrogenase Promoter from Penicillium Camemberti - Levican-Jaque, G; Sepulveda-Palma, F; Chavez-Rosales, R (2011)
The biotechnological applications of cheese-ripening fungi have been limited by a lack of genetics tools, in particular the identification and characterization of suitable promoters for protein expression. In this study, the suitability of the glyceraldehyde-3-phosphate dehydrogenase (gpdP) promoter from Penicillium camemberti to drive the production of a recombinant protein was evaluated. The gpdP gene and its promoter were isolated using PCR and Genome Walker. The promoter of gpdP has two regions with high identity to the regulatory elements gpd-box and ct-box previously described in Aspergillusnidulans. Two fragments of the promoter containing the gpd- and ct-box or the ct-box alone were used to drive the in vivo production of recombinant ?-galactosidase using A. nidulans as host. Our results indicate that larger fragment containing gpd-box enhances the production of ?-galactosidase activity levels respect to ct-box alone, and that both boxes are necessary to obtain maximal enzymatic activity production. The smaller fragment (187 nt) containing the ct-box alone was able to trigger up to 27% of ?-galactosidase activity, and to our knowledge this is the smallest fragment from a gpd gene used to produce a recombinant protein. Differences were not observed when glycerol, galactose or glucose were used as carbon sources, suggesting that the promoter activity is carbohydrate-independent. This is the first report in which a Penicillium gpd promoter is used for recombinant protein production. Our results open the way for the future development of a system for recombinant proteins expression in the biotechnologically important cheese-ripening fungus P. camemberti. © 2011 Springer Science+Business Media B.V.